2015
DOI: 10.1111/jnc.13265
|View full text |Cite
|
Sign up to set email alerts
|

Differential peptidomics assessment of strain and age differences in mice in response to acute cocaine administration

Abstract: Neurochemical differences in the hypothalamic-pituitary axis between individuals and between ages may contribute to differential susceptibility to cocaine abuse. This study measured peptide levels in the pituitary gland (Pit) and lateral hypothalamus (LH) in adolescent (age 30 days) and adult (age 65 days) mice from four standard inbred strains, FVB/NJ, DBA/2J, C57BL/6J, and BALB/cByJ, which have previously been characterized for acute locomotor responses to cocaine. Individual peptide profiles were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…) or a very small number of neuropeptides (Romanova et al . ) were detected. Neither of these two studies from Romanova and colleagues used heat‐stabilization of the brain tissue prior to peptide extraction, and without this treatment it is difficult to detect neuropeptides over the high background level of intracellular peptides (Svensson et al .…”
Section: Discussionmentioning
confidence: 96%
“…) or a very small number of neuropeptides (Romanova et al . ) were detected. Neither of these two studies from Romanova and colleagues used heat‐stabilization of the brain tissue prior to peptide extraction, and without this treatment it is difficult to detect neuropeptides over the high background level of intracellular peptides (Svensson et al .…”
Section: Discussionmentioning
confidence: 96%
“…In the brain, the arcuate nucleus of the hypothalamus processes POMC to produce the potent opioid peptide β-endorphin, and α-, β-, and γ-melanocortins [Ragavan et al, 1983;Rubinstein et al, 1996;Cowley et al, 2001;Romanova et al, 2015]. Besides the arcuate nucleus, POMC mRNA molecule has also been detected in several other mouse and rat brain regions, including the NAc, amygdala, hippocampus and cerebral cortex, in much lower levels than those in the arcuate nucleus [Civelli et al, 1982;Zhou et al, 1996Zhou et al, , 2013aLeriche et al, 2007;Bodnar, 2014;Granholm et al, 2017].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Rementioning
confidence: 99%
“…In order to allow time for dissection, especially of defined small brain structures, without using heat treatments, options such as “precooling” the brain by perfusing cold saline into the organ before dissection, 36 injecting cold modified Gey’s buffer salt solution into the body cavity immediately after euthanasia, 36,64 or fast sample freezing are effective. Although these methods reduce postmortem analyte degradation and are useful when precise anatomical areas need to be isolated, they do not prevent degradation without the need for additional stabilization methods.…”
Section: Resultsmentioning
confidence: 99%
“…27,3033 For example, experiments conducted by Stingl et al 21 and Segerström et al 34 demonstrated that heat stabilization effectively arrests the ex-viv o peptidase activity, thereby preserving the chemical sample composition as compared to samples from unstabilized tissues. Various means of heat stabilization, such as incubation in a hot water bath, 8,35,36 animal sacrifice by focused microwave irradiation (FMR), 26,29,37 microwaving of dissected tissue, 18 and laser-guided rapid conductive heating in a commercial device, the Denator Stabilizor T1 (ST1), 38,39 were previously investigated in a variety of neural and neuroendocrine tissues.…”
Section: Introductionmentioning
confidence: 99%